The cytoskeletal protein profilin is an important allergen in saltwort (Salsola kali) - Peterkova, Ludmila; Trifonova, Daria; Gattinger, Pia; Focke-Tejkl, Margarete; Garib, Victoria; Magbulova, Nigora; Djambekova, Gulnara; Zakhidova, Nodira; Ismatova, Mokhigul; Sekerel, Bulent Enis; Tuten Dal, Sevda; Tulaev, Mikhail; et al. (Frontiers in Immunology, 2024)
Pollen from Salsola kali, i.e., saltwort, Russian thistle, is a major allergen source in the coastal regions of southern Europe, in Turkey, Central Asia and Iran. Salsola kali allergic patients mainly suffer from hay-fever (i.e., rhinitis and conjunctivitis), asthma and allergic skin symptoms. Aim of this study was to investigate the importance of individual Salsola kali allergen molecules. Sal k 1, Sal k 2, Sal k 3, Sal k 4, Sal k 5, and Sal k 6 were expressed in Escherichia coli as recombinant proteins containing a C-terminal hexahistidine tag and purified by Nickel affinity chromatography. The purity of the recombinant allergens was analyzed by SDS-PAGE. Their molecular weight was determined by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and their fold and secondary structure was studied by circular dichroism (CD) spectroscopy. Sera from clinically well characterized Salsola kali-allergic patients were used for IgE-reactivity and basophil activation experiments. Salsola kali allergen-specific IgE levels and IgE levels specific for the highly IgE crossreactive profilin, and the calcium-binding allergen from timothy grass pollen, Phl p 12 and Phl p 7, respectively, were measured by ImmunoCAP. The allergenic activity of natural Salsola kali pollen allergens was studied in basophil activation experiments. Recombinant Salsola kali allergens were folded when studied by CD analysis. The sum of recombinant allergen-specific IgE levels and allergen-extract-specific IgE levels were highly correlated. Sal k 1 and profilin, reactive with IgE from 64% and 49% of patients, respectively, were the most important allergens whereas the other Salsola kali allergens were less frequently recognized. Specific IgE levels were highest for profilin. Of note, 37% of patients who were negative for Sal k 1 showed IgE reactivity to Phl p 12, emphasizing the importance of the ubiquitous cytoskeletal actin-binding protein, profilin, for diagnosis of IgE sensitization in Salsola kali-allergic patients. rPhl p 12 and rSal k 4 showed equivalent IgE reactivity and the clinical importance of profilin was underlined by the fact that profilin-monosensitized patients suffered from symptoms of respiratory allergy to saltwort. Accordingly, profilin should be included in the panel of allergen molecules for diagnosis and in molecular allergy vaccines.